Evaluation of Behavioral Factors Influencing Investors’ Investment Decisions in Nepal Stock Exchange (NEPSE) - Adhikari, Madhav; Bhusal, Suresh; Adhikari, Sangam; Sharma, Prerana (International Journal of Social Sciences and Management, 2025)
This study investigates the behavioral factors influencing investment decisions among individual investors in the Nepal Stock Exchange (NEPSE), focusing on four key biases: risk perception, loss aversion, overconfidence bias, and representative bias. Employing a descriptive and causal research design, data were collected from 250 investors in Kathmandu using a structured questionnaire. The study utilized a 5-point Likert scale to measure variables, and data were analyzed using descriptive statistics, correlation analysis, and multiple regression analysis in SPSS and MS Excel. The findings reveal that overconfidence bias has the strongest influence on investment decisions (β = 0.421), followed by risk perception (β = 0.183), representative bias (β = 0.144), and loss aversion (β = 0.119). All variables demonstrated significant correlations with investment decision-making, with overconfidence bias showing the highest correlation (r = 0.700). The regression model explained 59.1% of the variance in investment decisions, indicating a moderately strong relationship between the predictors and the dependent variable. The study highlights the pervasive impact of behavioral biases in shaping investment decisions, particularly in emerging markets like Nepal, where market inefficiencies and information asymmetries are prevalent. These findings contribute to the growing body of behavioral finance literature by providing empirical evidence from an under-researched context. Practical implications include the need for investor education programs to mitigate the effects of these biases, thereby promoting more rational and informed investment decisions. The study calls for further research to explore additional behavioral factors and their long-term impact on investment performance in NEPSE and similar markets. Int. J. Soc. Sc. Manage. Vol. 12, Issue-2: 77-88.